Listening to Fast-Tempo Music During a Post-Exercise Passive Rest Period Improved Subsequent Sprint Cycling. Issue 4 (August 2021) - Dobashi, Shohei; Matsuura, Fumiya; Ando, Daisuke
Listening to music during active recovery between exercise bouts has been found to help maintain high levels of exercise performance; however, the effect of listening to music alone with no exercise while resting passively has not been elucidated. We examined whether listening to music during static (passive) recovery affects subsequent repeated sprint performances and/or psychological and physiological responses in healthy young males. Twelve healthy young male athletes completed two consecutive sets of 7 × 7 second maximal cycling sprints with a 30-second rest interval between the sprints. During a 15-minute interval between the sets, the participants rested passively while listening to fast-tempo (Fast, 130 bpm), slow-tempo (Slow, 70 bpm) music, or no music (Con). We assessed affective valence and arousal using the Affect Grid. The valence and arousal scores immediately after listening to fast-tempo music were significantly higher than those in the no music condition. Mean and peak power outputs during the second set after listening to fast-tempo music were significantly higher compared to those after the Slow and Con conditions (both adjusted p < .05). Moreover, the changes in exercise performances between the first and second set were significantly associated with changes in the arousal score induced by the music conditions, but not with changes in the valence score. These results suggested that listening to fast-tempo songs during passive recovery between the exercises improved subsequent repeated sprint cycling performance in physically active males. This type of rapid exercise recovery might be useful for competitive athletes, such as judo, track and fields, and swimming races.